(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The skeleton is an important part of the human body. It provides a definite shape and definesthe stature of the human body along with it also plays an important role in forensic science. It aids forensic anthropologists in determining the age, sex and post mortem interval of the deceased person, if only the skeletal remains are found. This article reviews the techniques used for age estimation from different bones of human body. Forensic anthropologyis study of human skeletal remains to help determine the identity of the missing persons andto estimate time since death and age. There are various bones which help to determine the age range of the deceased like skull, clavicle and the pelvisregion. Radiographic methods arehelpful in examining these bones. There are around 300 bones present in a new born and as a person grows these bones start to fuse. At the age of 40 years all the bones fuse to make atotal of 206 bones. Bones start to ossify as the person ages and hence by studying the ossification of bones we can determine an age range for a person.